TRADE IN CLIMATE SMART GOODS OF ECUADOR: QUANTITATIVE ANALYSIS USING TRADE INDICES, SMART AND GRAVITY ANALYSIS - Mathur, Somesh K. (European Scientific Journal, ESJ, 2014)
The study identified Climate Smart Goods (CSG) in which Ecuador has advantage in production and trade. The interest in the subject of Trade in Climate Smart Goods was fuelled by Ecuador´s positive trade balance with the rest of the Andean Community and MERCOSUR region in 2010. SMART tool in WITS has been utilized for evaluating the relative benefits of tariff liberalization of CSG with MERCOSUR, China, Japan, US, and EU27 separately in 2010. It provides the results on various variables such as, trade creation, trade diversion, tariff revenue, and welfare and consumer surplus. Further, the study has also utilized a variant of Baier and Bergstrand (2001) gravity formulation for working out the basis of trade and export potential in CSG of Ecuador in 2010. The study concludes that trade in CSG will help Ecuador to promote alternative industries in the face of Global Economic Downturn. Also, it will help countries to look for safe, alternative and reliable energy source rather than believing in trade of crude and petroleum oil only or investing a great deal in nuclear energy. Ecuador can direct its social spending in promoting small industries which can provide CSG goods (low carbon emanating goods) at low cost. The Country-wise analysis reveals that for Ecuador, as far as trade in CSG is concerned, it is better to liberalize trade with the Japan, the US and the China, the main suppliers (exporters) of CSG products. The study also finds that there is export potential of 34 million US in CSG with respect to four Latin American trading partners of Ecuador. The four Latin American Countries are Bolivia, Chile, Columbia and Peru. This is less than the export potential when Ecuador liberalizes its trade of CSG with China, Japan and the US. Finally, on the basis of Gravity Analysis, some national and international policies are recommended for promoting CSG goods and limiting Climate change.